Unimas holds virtual exchange with Japanese students - Soubakeavathi, Rethinasamy; Samuel, Lihan; Dayang Hartijah, Abang Ahmad; Damien, Mikeng; Nurul Huzaimah, Hussien; Liyana, Rosli; Keezrawati, Mujan Yusuf; Joseph, Ramanair (The Star, 2021)
AN intercountry partnership continues to flourish despite the Covid-19 pandemic.